Design of a control moment gyroscope for small satellites - Tan, Calvin Xian Yang. (2013)
The primary aim of this project is to design a Control Moment Gyroscope (CMG) prototype for single axis control of an agile small satellite. The design should be small, compact and lightweight. Miniature motors and aluminum material were used to reduce the size and weight of the prototype. The overall prototype has a dimension of 12.5 x 12.5 x 12.5 cm and weighs 1.6 kg, which is significantly smaller and lighter than conventional CMG.